PERILAKU BALAP LIAR DI KALANGAN REMAJA DI BULAN RAMADHAN BERDASARKAN PERSPEKTIF PSIKOLOGI PERKEMBANGAN - Sadif, Ria Safaria; Taherong, Rosmawati; Kamil, Muhammad Aditsyan (Jurnal Multidisipliner Kapalamada, 2025)
This qualitative research examines the dynamics of teenagers' illegal racing behavior in Baubau City during Ramadhan from a developmental psychology perspective. Through a case study with semi-structured interviews and observations of 5 participants, it was found that this behavior is influenced by factors of identity search, peer influence, need for social recognition, and risk assessment bias. The context of Ramadhan with its changing activity patterns exacerbates this tendency. Findings revealed weak internalization of spiritual values, moral immaturity, and lack of parental supervision as driving factors. This study emphasizes the need for interventions based on adolescent psychological development that include: (1) risk education programs, (2) provision of alternative activities, and (3) contextual strengthening of moral values. This study provides important insights for addressing adolescent deviant behavior by considering developmental dimensions and specific socio-cultural contexts.